Accounting Information System for Depreciation of State Property Using the Straight Line Method at KPP Pratama Medan Timur - Rangkuti, Siti Aisyah (IHSA Institute, 2023)
Accounting Information System (AIS) is a system that aims to collect data and report information relating to financial transactions. Fixed Assets are tangible goods belonging to the company which are relatively permanent in nature and are used in the normal activities of the company, not for sale and purchase. In this system an application will be designed to calculate the depreciation of state property using the straight-line method using the Microsoft Visual Basic 2008 programming language and the Microsoft SQL Server 2005 database. accurate..